The Health Consequences of Power Outages - Electricity Load-Shedding Problem in Country - Syed Zulfiquar Ali Shah, Muhammed Kashif Shaikh, Nusrat Nisar, Ishrat Bibi, Isra Gill, Fareeha Ali, Nudrat, (Pakistan Journal of Medical & Health Sciences, 2023)
Electricity powers the economic system. Households need stable electricity since many tasks require it1. Pakistan had frequent power outages for decades. The monopolistic supplier used cyclical load shedding over many hours a day in much of the country to avoid unplanned blackouts and meet power demand due to power production losses. Load shedding occurs when power demand exceeds the supply2. Pakistan's major power resource for heating, cooking, and lighting is electricity, although load shedding's economic impacts are mostly highlighted due to the country's difficult economic circumstances. Health effects and expenses are poorly documented. This is concerning because hospital reports relate blackouts to health effects, such as excessive stress on already overburdened personnel after procedures2. For individuals who try to deal with electricity, unannounced load shedding is worse. Protesters block highways over power cuts. The police have confirmed lots of crime in big cities. Power interruptions disrupt industrial consumers' regular operations. Power failures shuttered tube wells and water pumps, affecting water supply and mills.3 Electrical network breakdowns raise hospitalizations, health problems, and death, while natural calamities and severe weather events which were followed by power outages, damaged the population's overall well-being by increasing emergency admissions4.